Hyponatraemia in older medical patients: implications for falls and adverse outcomes of hospitalisation. Issue 10 (October 2014) - Ahamed, S.; Anpalahan, M.; Savvas, S.; Gibson, S.; Torres, J.; Janus, E.
Abstract Background Recent evidence suggests an association between hyponatraemia and falls. Aims To determine the association of hyponatraemia with admission‐associated falls (i.e. falls as part of the presenting complaint or during admission) and predefined adverse outcomes of hospitalisation. Methods A case–control study of patients aged ≥65 years admitted with hyponatraemia during a 6‐month period was conducted. The relevant data were collected by review of medical records and analysed in univariate and multivariate models. Results The prevalence of hyponatraemia was 22% and more likely to be associated with the admission diagnoses of cardiovascular (P = 0.04) and metabolic disorders (P < 0.001), use of diuretics (P = 0.037) and a higher Charlson comorbidity score (P = 0.035). Hyponatraemia was independently associated with admission‐associated falls (odds ratio (OR) 3.12, confidence interval (CI) 1.84–4.38, P < 0.001). The increased odds of falling were similar for mild (OR 3.15, CI 1.75–5.66) vs moderate to severe hyponatraemia (OR 3.07, CI 1.57–6.03). Although hyponatraemia had a significant independent association with increased length of stay (LOS) (OR 1.48, CI 1.22–1.79, P < 0.001) and change in residential care status to a more dependent category at discharge (OR 4.28, CI 1.68–10.859, P = 0.002), it was not associated with mortality or time to first unplanned readmission. Hyponatraemia was significantly associated with the need for inpatient rehabilitation; however, this was no longer significant when adjusted for falls. Conclusion Hyponatraemia is independently associated with increased risk of admission‐associated falls. The degree of falls risk is similar regardless of the severity of hyponatraemia. Hyponatraemia is also an important determinant of many adverse outcomes of hospitalisation.